Evaluation of diaphyseal osteotomies for correction of moderate to severe hallux valgus: Scarf and Modified Chevron osteotomies - Guerrero Forero, Santiago; Rodríguez Ciodaro, Ricardo; Valcárcel, Paula Andrea; Marulanda Soto, David (Revista Colombiana de Ortopedia y Traumatología, 2016)
Background: The aim of the study was to compare functional and radiological outcomes during the first postoperative year between two different first metatarsal osteotomies (modified Chevron vs. Scarf) in patients with moderate and severe hallux valgus, in Hospital de San José between January 2010 and January 2013. Materials and methods: An observational cohort study was conducted on the radiological measurements pre-operatively, at 6 weeks post-operatively, and at 12 months. The functional measurements were made pre-operatively and at 12 months postoperatively, using the American Orthopaedic Foot and Ankle Society (AOFAS) scale. A comparison was made of the two diaphyseal first metatarsal osteotomies in patients with moderate and severe hallux valgus, performed randomly by three sub-specialists surgeons in foot and ankle surgery. Results: A total of 69 feet were included from 57 patients with a mean age of 50.8 years, who underwent, equally, one of the two selected surgical techniques. No significant differences were found between the two techniques on comparing the radiological measurements and AOFAS functional scale at 6 weeks and 12 months. There was higher recurrence rate for the modified Chevron technique, 19.35% compared with 5.26% with the Scarf. Discussion: The comparison of radiological and functional measurements at 1 year follow-up between Chevron and Scarf osteotomies to correct moderate to severe hallux valgus in the Hospital of San José show similar results, but the recurrence rates for modified Chevron technique are three times higher than those found in treatment with Scarf osteotomy. Evidence level II.